Fever of War : the Influenza Epidemic in the U.S. Army during World War I. - Byerly, Carol R. (NYU Press, 2005)
The influenza epidemic of 1918 killed more people in one year than the Great War killed in four, sickening at least one quarter of the world's population. In Fever of War, Carol R. Byerly uncovers the startling impact of the 1918 influenza epidemic on the American army, its medical officers, and their profession, a story which has long been silenced. Through medical officers' memoirs and diaries, official reports, scientific articles, and other original sources, Byerly tells a grave tale about the limits of modern medicine and warfare. The tragedy begins with overly confident medical officers.